Human Resource Management and Job Performance among Senior Secondary School Teachers in Oyo Metropolis, Nigeria. - Lateef, A. Y. (International Journal of Educational Management, 2022)
This study examined human resource management practices and job performance among senior secondary school teachers in Oyo metropolis in Nigeria. Specifically, the study investigated the contributions of teacher motivation and teacher development to teacher job performance. Two research questions guided the study. This study was adopted a descriptive survey research design. A total of 96 participants across 24 senior secondary schools were sampled using stratified random sampling technique. Data were collected using a validated and well structured instrument tagged Human Resource Management–Teacher Job Performance Questionnaire “HRM-TJPQ” (reliability index r=0.82, test re-test of 3 weeks interval). Data were analyzed using Multiple Regression Analysis Statistics. Results showed positive and significant association between the combined independent variables (teacher motivation, teacher development) and teacher job performance. Results indicated that teacher motivation (Beta=0.375) had the highest contribution to teacher job performance, followed by teacher development (Beta=0.316), in that order. Based on the findings, it was recommended that teachers must be well motivated in terms of recognition and incentive scheme for exceptional teacher job performance. Also, government must encourage teacher capacity development in order to attain greater proficiency.